Investigation of Aflatoxin M1 in Milk Powder Marketed in Karachi, Pakistan - Raza, Rashid (Journal of Research (Science), 2025)
Aflatoxins are strong toxic and cancer producing substance which can be excreted in lactating humans in the form of aflatoxin M1 (AFM1), exposed to food contaminated with mycotoxins. In the current study a total of 35 powdered milk samples (15 full cream instant milk powder and 20 infant milk powder) were analyzed for the detection of aflatoxin M1and results were compare with the standard upper allowable limits of AFM1. All samples of full cream powdered milk (branded and unbranded) and infant formula milk powder were found to be contaminated with AFM1 with an average level 104.3, 120.5, 125.0ng/kg respectively. The AFM1 contamination level were found in a range of 28–166ng/kg for branded full cream milk powder, 43–254ng/kg for unbranded full cream milk powder and 17-164ng/kg for infant formula milk powder, respectively. In total, three samples (60%) of full cream branded, 6 samples (60%) unbranded milk Powder and 15 samples (75%) of infant milk powder samples exceed European Union (EU) and the US regulations. Two of the samples (40%) full cream branded and five samples (50%) of unbranded milk Powder and seven samples (75%) of infant milk powder samples of were found exceeding the upper limits set for Pakistan by Pakistan Standards and Quality Control Authority (PSQCA). Aflatoxin M1 is the most widely distributed mycotoxin in milk-based foodstuffs and has potential carcinogenic effects. Therefore, it is necessary to monitor milk and milk products for contamination levels of AFM1.